Presidential Address: The Personal and the Historical - Fingard, Judith (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1998)
AbstractIn her 1998 Presidential Address to the Canadian Historical Association, Judith Fingard poses a question which has been on our collective minds for some time: “Does the personal history of the historian determine the choice of her or his subject matter, approach, and ongoing professional development?” By delving into the personal reflections of celebrated Canadian historians, Fingard has been able to shed light on this contentious issue. According to Fingard, the personal and professional intersect at several key points (or at least have for her sample of historians working in Canada in the past twenty years). The obvious, it seems, is true. Gender, class and stage of life all influence scholarly pursuits whether it be in terms of subject matter chosen or the amount of time one is able to devote to research and writing. Certainly the past twenty years has seen great change in Canadian academia; particularly, one can argue, in the field of history. It is clear that those sampled in Fingard's survey drew upon their personal backgrounds not only to forge a passion for the past - sometimes against all odds - but a professional identity based on the study of history of the margins. Ultimately, we can conclude that social historians of the past twenty years personify the field they played such a role in developing. To varying degrees, the profession is indeed personal.